Transmedia educommunication method for social sustainability in low-income communities - Tárcia, Lorena; Alzamora, Geane Carvalho; Cunha, Leo; Rampazzo Gambarato, Renira (Frontiers in Communication, 2023)
In the post-pandemic world, we see the exacerbation of digital connections but also inequalities between countries with higher or lower degrees of access to fast Internet services. Digitization processes enable and intensify global exchanges and yet expand disconnections as they globalize debates and solutions without considering the different levels of accessibility, digital literacy, and Internet infrastructure in less privileged communities. Such discrepancies are reflected in learning levels and, consequently, in the development of social sustainability. As a theoretical-methodological contribution, this paper draws on the concepts of transmedia logic, educommunication, and social sustainability. The original transmedia educommunication method discussed here consists of a week-long gamified intervention in schools with students between 11 and 14 years old. Through this experience, we aim to develop media and text literacy skills in students and teachers. Our objective is to give them the tools to distinguish between textual genres and their purposes. The article details the development and application of this method in Portuguese speaking countries.